2019
DOI: 10.3389/fpubh.2019.00145
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of U.S.-Based Colorectal Cancer Screening Uptake Intervention Systematic Reviews: Available Evidence and Lessons Learned for Research and Practice

Abstract: Background: We examined colorectal cancer screening (CRCS) intervention effectiveness, through the effect sizes associated with: (1) screening modality, (2) intervention level (e.g., client-directed), and (3) intervention component (e.g. client reminders) within published CRCS intervention systematic reviews (SRs). Methods: A search of peer-reviewed CRCS SRs that were written in English was employed utilizing five databases: CINAHL, Cochrane Library, rTIPS, PubMed, and PsycIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Some studies did not report odds ratios so the decision was made to calculate odds ratios for all studies based on the data presented in each article. A systematic review of U.S.-based CRC screening interventions reported that CRC screening interventions which include a combination of screening methods might be most effective; however, most clinic-based interventions might need to provide the array of screening options if they are part of their menu of services [47]. Some clinics, such as federally-qualified health centers (FQHC), might only provide stool blood testing and referral to colonoscopy, so these types of clinics would be more likely to be study sites for a stool blood testing approach only.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Some studies did not report odds ratios so the decision was made to calculate odds ratios for all studies based on the data presented in each article. A systematic review of U.S.-based CRC screening interventions reported that CRC screening interventions which include a combination of screening methods might be most effective; however, most clinic-based interventions might need to provide the array of screening options if they are part of their menu of services [47]. Some clinics, such as federally-qualified health centers (FQHC), might only provide stool blood testing and referral to colonoscopy, so these types of clinics would be more likely to be study sites for a stool blood testing approach only.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A combination of the FOBT and lower-GI endoscopy (sigmoidoscopy/colonoscopy) could increase the accuracy of screening programs for the detection of colorectal neoplasia, suggesting combination methods as the most effective CRC screening method [227,228]. In addition, considering risk stratification to identify high-risk individuals was suggested to increase the effectiveness of CRC screening programs.…”
Section: Combination and Risk-based Strategiesmentioning
confidence: 99%
“…The third pivotal diagnostic branch, laboratory medicine, is also deeply involved in cancer diagnostics. Its current contribution is minimal for the diagnosis, at least compared to that provided by pathology and radiology, since it is almost limited to assessment of a narrow number of biomarkers such as prostate specific antigen (PSA) for prostate cancer screening, human papilloma virus (HPV) molecular diagnostics for the screening of cervical cancer, or faecal occult blood test (FOBT) for colorectal cancer screening (46)(47)(48). The vast majority of other molecular or phenotypic biomarkers that can be measured in routine clinical laboratories are instead used for disease monitoring and for guiding prognostic and therapeutic decisions (49).…”
Section: Integrated Diagnostics In Cancermentioning
confidence: 99%